2010
DOI: 10.1590/s0104-42302010000600011
|View full text |Cite
|
Sign up to set email alerts
|

Incontinência urinária de esforço em mulheres pertencentes ao Programa de Saúde da Família de Dourados (MS)

Abstract: StreSS urinary incontinence among women participating in the family health program of DouraDoS (mS), Brazil 649Rev Assoc Med Bras 2010; 56(6): 649-54 IntroductIonUrinary incontinence (UI) is defined as involuntary loss of urine through the urethra. 1 This condition can be classified into three common types: stress urinary incontinence (SUI), urge urinary incontinence (UUI), and mixed urinary incontinence. In SUI, urine leakage occurs when there is increased intraabdominal pressure, such as while practicing phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 45 publications
0
10
0
7
Order By: Relevance
“…8,10,14,30 In our study, SUI affected 15.9% of climacteric women and was similar to the population findings by Brito et al 8 With regard to factors associated with UI, the literature is controversial and often shows association between UI and socio-demographic data such as age, education and race; obstetric factors such as pregnancy, multiparity, type of delivery, newborn weight; gynecological factors such as gynecological surgeries and menopausal status; and morbidities such as diabetes mellitus and obesity. 1,4,[27][28][29][30][31] The bivariate analysis performed in our study showed a positive association with education, skin color, pregnancy, gynecologic surgery, which was not confirmed in the logistic regression. Our findings are in line with those documented by Brito et al 8 and Guarisi et al, 14 who also found no association between UI and socioeconomic and reproductive factors.…”
Section: Discussionmentioning
confidence: 99%
“…8,10,14,30 In our study, SUI affected 15.9% of climacteric women and was similar to the population findings by Brito et al 8 With regard to factors associated with UI, the literature is controversial and often shows association between UI and socio-demographic data such as age, education and race; obstetric factors such as pregnancy, multiparity, type of delivery, newborn weight; gynecological factors such as gynecological surgeries and menopausal status; and morbidities such as diabetes mellitus and obesity. 1,4,[27][28][29][30][31] The bivariate analysis performed in our study showed a positive association with education, skin color, pregnancy, gynecologic surgery, which was not confirmed in the logistic regression. Our findings are in line with those documented by Brito et al 8 and Guarisi et al, 14 who also found no association between UI and socioeconomic and reproductive factors.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, with changes in life expectancy and lifestyle, other factors have emerged, such as chronic diseases and the medications used to treat them 7 . In Brazil, there is an increasing interest in the prevalence, risk factors and distribution of female UI [8][9][10][11][12] . Women living in urban areas in the Midwest region and in the Southeast region of the country present a prevalence of UI ranging from 21.4% to 32.9% [9][10][11][12] .…”
mentioning
confidence: 99%
“…In Brazil, there is an increasing interest in the prevalence, risk factors and distribution of female UI [8][9][10][11][12] . Women living in urban areas in the Midwest region and in the Southeast region of the country present a prevalence of UI ranging from 21.4% to 32.9% [9][10][11][12] . Those with a higher number of pregnancies and births and with a higher body mass index (BMI) have a greater risk of developing UI 12 .…”
mentioning
confidence: 99%
“…Estudos no Brasil também apresentam variações de prevalência (Guarisi et al, 2001;Tamanini et al, 2009;Gomes, Silva, 2010;Santos C, Santos V, 2010;Burti et al, 2012;Menezes et al, 2012;Cinara Sacomori et al, 2013).…”
Section: Introductionunclassified
“…Em mulheres climatéricas do município de Campinas, a prevalência de IUE foi de 35% (Guarisi et al, 2001), enquanto que em Dourados, Mato Grosso do Sul, foi de 21,4% entre mulheres acima de 20 anos de idade (Gomes, Silva, 2010).…”
Section: Introductionunclassified